Pengembangan Multimedia Interaktif Materi Sifat-Sifat Segi Banyak Beraturan Dan Segi Banyak Tidak Beraturan Untuk Menumbuhkan Kemampuan Berpikir Kritis Siswa Kelas IV Sekolah Dasar - Wilujeng, Reni; Primasatya, Nurita; Damayanti, Susi (Efektor, 2022)
Based on the results of the observation implemented in IV class of SDN Nglawak 1, Prambon district, Nganjuk regency, in learning process the teacher did not use learning media but only used lecturing and question and answer method, so learning is still monotonous. This study aims to determine the validity, practicality, and effectiveness of interactive multimedia. The method used in this study is ADDIE model, the data analysis technique used in the form of quantitative and qualitative with research subjects is 6 fourth grade students at SDN Nglawak 1. The results of research are as follows: 1) interactive multimedia is called to be valid by obtaining the percentage of media experts is 80%, while the percentage of material experts is 85%; 2) interactive multimedia was declared to be effective by obtaining a completeness percentage of 84%; 3) interactive multimedia is said to be practical by obataining a percentage of teacher questionnaires is 88% and student questionnaires is 92%. Out of these results, it can be concluded that interactive multimedia on mathematics material can be used in the teaching learning process of fourth grade elementary students, the use of interactive multimedia can make it easier for students to understand the material properties of regular polygons and irregular polygons.